The middle east and north africa diagnosis and management guidelines for inborn errors of immunity - ÖZEN, AHMET OĞUZHAN (My University, 2022)
Human inborn errors of immunity (IEI) are a group of 485 distinct genetic disorders affecting children and adults. Signs and symptoms of IEI are heterogeneous, and accurate diagnosis can be challenging and depends on the available human expertise and laboratory resources. The Middle East and North Africa (MENA) region has an increased prevalence of IEI because of the high rate of consanguinity with a predominance of autosomal recessive disorders. This area also exhibits more severe disease phenotypes compared with other regions, probably due to the delay in diagnosis. The MENA-IEI registry network has designed protocols and guidelines for the diagnosis and treatment of IEI, taking into consideration the variable regional expertise and resources. These guidelines are primarily meant to improve the care of patients within the region, but can also be followed in other regions with similar patient populations.
Keywords: Inborn errors of immunity; Primary immunodeficiency; Diagnosis; Treatment; MENA region